Monomeric annexin A2 is an oxygen-regulated toll-like receptor 2 ligand and adjuvant. Issue 1 (December 2016) - Andersen, Brian; Xia, Junzhe; Epstein, Alan; Ohlfest, John; Chen, Wei; Blazar, Bruce; Pennell, Christopher; Olin, Michael
Abstract Background Annexin A2 (ANXA2) is a pleiotropic, calcium-dependent, phospholipid-binding protein with a broad tissue distribution. It can be intracellular, membrane-bound, or secreted, and it exists as a monomer or heterotetramer. The secreted ANXA2 heterotetramer signals human and murine macrophages to produce IL-1, IL-6, and TNF-α through TLR4/MyD88- and TRIF-dependent pathways. Methods GL261 glioma cells were cultured in 5 % or 20 % O2 . Monomeric ANXA2 (ANXA2m) was identified as a TLR2-binding protein enriched in 5 % O2 by mass spectrometry. Purified ANXA2m and ANXA2-derived peptides were added to TLR2-expressing reporter cells and immature dendritic cells (DCs) cells in vitro. ANXA2m was then mixed with chicken ovalbumin (OVA) for vaccination ofTLR2 +/+ andTLR2 −/− mice for subsequent quantification of antigen-specific CD8+ T cell responses. The TLR2-binding region of ANXA2m was determined using various peptides derived from the ANXA2 amino terminus on TLR2 reporter cells and in vaccinated mice. Results ANXA2m is overexpressed by murine glioblastoma GL261 cells grown under 5 % O2, but not atmospheric 20 % O2, and acts as an adjuvant by inducing murine and human DC maturation through TLR2. ANXA2m upregulates CD80 and CD86 expression, enhances antigen cross-presentation, and induces the secretion of IL-12p70, TNF-α, and IFN-γ. The amino-terminal 15 amino acids of ANXA2m are necessary and sufficient for TLR2 binding and DC activation. Conclusion This novel finding adds to the known functions of ANXA2 and suggests ways to exploit it as a vaccine adjuvant. ANXA2-antigen fusion peptides could be developed for patients as "off-the-shelf" agents containing common tumor antigens. Alternatively, they could be "personalized" and synthesized after tumor sequencing to identify immunogenic tumor-specific neo-antigens. As the amino terminal 15 amino acids of ANXA2 are required to stimulate TLR2 activity, a fusion peptide could be as short as 30 amino acids if one or two CD8 T cell epitopes are fused to the ANXA2 amino terminal portion. Future work will address the efficacy of ANXA2 peptide fusions alone and in combination with established TLR agonists to induce synergy in preclinical models of glioma as observed in other vaccines.